(untitled) (Journal of Pharmaceutical Negative Results, 2023)
According to the 2011 Census, India had a population of 121.06 billion people, of whom 48.5% were female. In 2011, the sex ratio in India was 943, while it was 949 and 929 in rural and urban regions, respectively. In the following research, an effort has been made to comprehend the demographic status of women in six sample villages in the Belagavi district of Karnataka State. In the current research, the villages chosen for the aforesaid purpose are namely Amboli in Khanapur taluka, Bandarahalli in Soundatti taluka, Dodwad in Athani taluka, Perawadi in Chikkodi taluka, Rangapura in Gokak taluka, and Yaragoppa in Bailhongal taluka. The basic information for each of these villages is taken from the district census handbook, and micro-level village data has also been used to illustrate the overall picture of each village's demographic characteristics. The maps were obtained from the study's village accountant and are used to describe the topographical setting and land usage of each village. Before conducting the required interpretation, the relevant demographic data has been scientifically analysed and represented in tabular format. Graphs and diagrams have also been used to illustrate demographic variables such as population growth, density and sex ratio.